Handbook of budgeting - Rachlin, Robert (John Wiley & Sons, 1999)
Without clearly outlined budgets, corporations are unable to predict profits or losses or create plans for the future. This handbook shows controllers and budget directors how to create any style of budget, from the traditional approach to the cutting-edge, activity-based approach. No other management tool provides the operational direction that a well-planned budget does, and no other book provides such a complete guide to preparation, presentation, analysis, and effective use.